The Protestant Peril"" : The Church and Italian Catholics on the issue of religious freedom, 1922-1955 - Zanini, Paolo (Modern Catholicisms, 2025)
In Italy, anti-Protestantism became a relevant motif of reactionary polemics during the Risorgimento and the post-unification period in the 19th century. Attenuated around 1900, the anti-Protestant offensive resumed after the First World War. Between the early 1920s and the mid-1950s, the hostility of the Catholic Church towards the Protestant presence and mission in Italy became a significant social and political phenomenon. It succeeded in influencing the attitude of the Italian state and the legislation on religious freedom itself. Reconstructing Catholic anti-Protestantism, Paolo Zanini shows that the attitude towards Protestant denominations was one of the features of continuity between Fascism and the first decade of the post-war Republic.